Bromide Ions Triggered Synthesis of Noble Metal–Based Intermetallic Nanocrystals. Issue 40 (2nd September 2020) - Wang, An‐Liang; Zhu, Lijie; Yun, Qinbai; Han, Sumei; Zeng, Li; Cao, Wenbin; Meng, Xiangmin; Xia, Jing; Lu, Qipeng
Abstract: Ordered intermetallic nanomaterials with a well‐defined crystal structure and fixed stoichiometry facilitate the predictable control of their electronic structure and catalytic performance. To obtain the thermodynamically stable intermetallic structures, the conventional approaches with high‐temperature annealing are still far from satisfactory, because of annealing‐induced aggregation and sintering of nanomaterials. Herein, a general wet‐chemical method is developed to synthesize a series of noble metal–based intermetallic nanocrystals, including hexagonal close‐packed (hcp) PtBi nanoplates, face‐centered cubic (fcc) Pd3 Pb nanocubes, and hcp Pd2.5 Bi1.5 nanoparticles. During the synthetic process, Br − ions play two important roles for the formation of ordered intermetallic structures: i) Br − ions can coordinate with the metal ions to decrease their reduction potentials thus slowing down the reduction kinetics. ii) Br − ions can combine with molecular oxygen to generate an oxidative etching effect, hence reconstructing the atom arrangement, which is beneficial for the formation of the intermetallic structure. As a proof‐of‐concept application, Pd3 Pb nanocubes are used as electrocatalysts for ethanol and methanol oxidation reactions, which exhibit significantly improved electrochemical performance compared with the commercial Pd black catalyst. Abstract : A general wet‐chemical method is developed to synthesize a series of noble Metal–Based intermetallic nanocrystals, in which Br − ions play important roles in the formation of atomically ordered structures. The obtained Pd3 Pb nanocubes exhibit superior electrocatalytic performance for ethanol and methanol oxidation reactions.